Traumatic brain injury: The first 15 milliseconds. (5th December 2016) - Martin, Graham
Abstract: Objective : The physical events of the first 15 milliseconds of a traumatic brain injury are reviewed from computer simulations using finite element calculations and applied to observed pathology. Methods : The impact creates two shock waves; one through the brain, another through the skull, both injure the brain separately. Two accelerations, anteroposterior and rotary, distort or stretch the brain, because of inertia. The two shockwaves are reflected many times within in the brain, from boundaries where the density or elasticity changes. Results : Overlapping waves form powerful positive or negative pressure nodes. Negative waves are more damaging to neurones and blood vessels, so a random pattern of scattered neural and capillary necroses develop all over the brain. The skull shockwave expands the skull opposite the blow, so creating a damaging negative pressure injury to the brain, contre coup contusion. Acceleration (or deceleration) follows impact, beginning later and lasting longer. Inertia strains the tissue, where the brain is free to move, inflicting characteristic white matter injuries. Conclusions : In the antero-posterior plane, acceleration and inertia stretch and tear long tracts to the spine and blood vessels running from the brain to the dura. Rotatory accelerations stress the inter-hemispheric connections of the brain, especially the corpus callosum, between the hemispheres.